Chemically modified oil palm ash‐filled natural rubber composites and its properties. Issue 4 (31st October 2013) - Ooi, Zhong Xian; Ismail, Hanafi; Abu Bakar, Azhar
<x xml:space="preserve">Abstract</x> Chemically modified Oil Palm Ash (OPA)‐filled natural rubber composites were prepared by modifying the functional group of OPA with cetyltrimethylammonium bromide (CTAB) prior to compounding by using laboratory conventional laboratory‐sized two‐roll mills. The functional groups of CTAB‐modified OPA were analyzed by using Fourier Transform Infrared (FTIR) and compared with those of non‐modified ones. The CTAB‐modified OPA‐filled NR composites showed shorter scorch time and cure time as compared to those of non‐modified OPA, which was attributed to the new functional groups occurred. The tensile test results showed that the OPA‐filled NR composites with CTAB modification exhibit improvement in tensile strength, tensile modulus, and hardness but lower elongation at break as compared to nonmodified ones. The tensile fractured surface of modified OPA filled NR composites revealed the well embedded and better distribution of CTAB‐modified OPA in NR matrix. The toluene uptake was also found to be lower for the modified OPA‐filled NR composites and showed better rubber–filler interaction; it further showed that surface modification with CTAB could compatibilize the OPA particles and NR matrix. POLYM. COMPOS., 35:691–697, 2014. © 2013 Society of Plastics Engineers